188 Changes in Perivascular Adipose Tissue in Ageing and Atherosclerotic Mice. (3rd June 2016) - Walker, Rachel; Austin, Clare; Holt, Cathy
Abstract : Perivascular adipose tissue (PVAT) encases the majority of blood vessels and is an important component of the vasculature. PVAT is an active endocrine organ but until recently was not considered important in the pathogenesis of atherosclerosis. In healthy vessels PVAT exerts an anti-contractile effect which is attenuated in states of metabolic disturbance. The following experiments were conducted to determine the influence of PVAT, age and progression of atherosclerotic disease on isolated arterial reactivity. Upon weaning, male ApoE -/- or C57/BL6 (control) mice were fed a standard rodent chow diet for a period of eight or twenty-six weeks. Aortic atherosclerotic lesion area was analysed by en face quantification with Oil Red O. Aortic PVAT was collected and weighed. Contractile responses of the thoracic aortae to cumulative doses of phenylephrine (1 × 10 –10 – − 3 × 10 –5 M) were measured in PVAT intact or PVAT denuded vessels using myography. Adipokine expression from PVAT was examined using an adipokine proteome profiler. Atherosclerotic lesions were present in the aortae of the ApoE -/- mice. A significant increase in total lesion area occupying the aorta was observed in the aged ApoE -/- mice compared to mice at the earlier time-point (0.11% vs. 2.78%, P = 0.006, n = 6–7 mice per group). A significant increase in the amount of PVAT surrounding the aortae of C57/BL6 mice was recorded in response to ageing (15.65 ± 2.90 mg versus 26.87 ± 2.84 mg, P = 0.02 n = 5–8 mice per group). In contrast, no differences in the amount of aortic PVAT was observed between young and ageing ApoE -/- mice (14.08 ± 1.64 mg versus 13.11 ± 1.78 mg, P=NS, n = 3–5). Aortic PVAT exerted anti-contractile effects in the young 8 week controls (PVAT versus no PVAT: P = 0.04, n = 6). However, the anti-contractile capacity of aortic PVAT was abolished in ageing control mice (PVAT versus no PVAT: P=NS, n = 8). The aortic PVAT from young ApoE -/- mice exhibited the characteristics of an aged phenotype, exerting no anti-contractile effect (PVAT versus no PVAT: P=NS, n = 8); this was sustained in ageing ApoE -/- mice (PVAT versus no PVAT: P=NS, n = 8). Modulations in adipokine expression were observed with ageing in both C57/BL6 and ApoE -/- mice. Aortic PVAT from ApoE -/- mice displayed an aged phenotype even at 12 weeks of age. These findings may have important implications in the pathogenesis of atherosclerosis. Further investigation into the characteristics of aortic PVAT from ApoE -/- mice and the factors it releases in early and established atherosclerosis is ongoing. This research was funded by the British Heart Foundation.